Effect of a six-week times restricted eating intervention on the body composition in early elderly men with overweight - Przemysław Domaszewski; Mariusz Konieczny; Paweł Pakosz; Katarzyna Łukaniszyn-Domaszewska; Wioletta Mikuláková; Ewa Sadowska-Krępa; Steve Anton (Scientific Reports, 2022)
Abstract The main aim of the study was to determine the effectiveness of time-restricted eating (TRE) in reducing body fat and lowering body mass index in early elderly men with overweight (65–74 years). An additional goal was to determine the feasibility of applying TRE for extensive use in elderly men. This study included a group of 46 healthy men (EXP = 23 persons, CON = 23 persons). The six-week intervention in the experimental group involved complete abstinence from food intake for 16 h per day, from 08:00 to 12:00 p.m. After the intervention, the body weight decreased in the EXP group (− 1.92 kg) with a 95% CI (1.14–2.70) compared to the CON group. There was also a decrease in the Visceral fat mass (− 0.64 l) with 95% CI (0.46–0.82) and in the waist circumference (− 3.11 cm) with 95% CI (1.89–4.33) in the EXP group compared to the CON group. The skeletal muscle mass did not change significantly. There was no significant change in the control group, either. The application of TRE in early elderly overweight men resulted in positive changes in body composition and visceral fat. All participants succeed in the prescribed diet plan, which shows that TRE is easy to maintain for early elderly overweight men and may become an essential obesity treatment tool in these age groups.